Exploring the Relationship Between Allergic Rhinitis and Otitis Media with Effusion: A Scoping Review - Adnan Abdullah; Nurcholid Umam Kurniawan; Rizky Firmansyah; Dewi Yuniasih (JURNAL IMPLEMENTA HUSADA, 2026)
Allergic Rhinitis (AR) and Otitis Media with Effusion (OME) are two prevalent conditions that often co-occur, particularly in pediatric populations. AR is characterized by inflammation of the nasal mucosa in response to allergens, while OME involves fluid accumulation in the middle ear, which can lead to hearing loss and developmental delays in children. This study employed a scoping review design to explore the relationship between Allergic Rhinitis and Otitis Media with Effusion (OME). Relevant articles were identified through a purposive search of the Scopus database using keywords such as “Allergic Rhinitis” and “Otitis Media with Effusion.” Articles were included if they were original research, reviews, meta-analyses, or systematic reviews published between 2020 and 2024 in English. The PRISMA flow diagram was used to guide the selection process. From an initial 215 records, 12 articles met the eligibility criteria and were included in the final review. The finding indicate that allergic rhinitis is a major risk factor for OME, particularly in children. Other contributing factors include adenoid hypertrophy, smoke exposure, daycare attendance, GERD, and LPR. Inflammatory processes and Eustachian tube dysfunction were commonly identified mechanisms. Several studies reported that treating allergic rhinitis and related comorbidities improves OME outcomes, while surgical interventions like adenoidectomy and ESS also showed clinical benefits. Further investigation into the pathophysiology of AR and OME is needed to develop better clinical interventions and improve patient outcomes.